Bosnia and Herzegovina : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2010)
Threats to external stability in the pre-crisis period have now been reduced substantially and foreign non-debt creating flows have declined, sufficient to support external stability. The global economic downturn has raised challenges for evaluating the countries' fiscal stance and fiscal policy focus should be lowering support to debt sustainability, private sector development, and the currency board stability. The two entity pension funds have been under increasing financial pressures. Putting the public pension systems on a sound footing will encompass a number of complementary steps.